Ginsenoside Rc ameliorated atherosclerosis via regulating gut microbiota and fecal metabolites - Xie, Bin; Zu, Xianpeng; Wang, Zhicong; Xu, Xike; Liu, Guoping; Liu, Runhui (Frontiers in Pharmacology, 2022)
Atherosclerosis (AS) and the accompanied cardiovascular diseases (CVDs) were leading cause of death worldwide. Recently, the association among CVDs, gut microbiota and metabolites had aroused increasing attention. In the study, we asked the underlying mechanism of Ginsenoside Rc (GRc), an active ingredient of ginsenosides used for treatment of CVDs, in apolipoprotein E-deficient (ApoE-/-) mice with high fat diet (HFD). 7-week-old male ApoE-/- mice were randomly divided into four groups: the normal control (NC) group, the HFD group, the GRc group (40 mg/kg/d) and the atorvastatin (Ato) group (10 mg/kg/d). Atherosclerotic injury was evaluated by aortic lesions, serum lipid levels and inflammatory factors. The composition of gut microbiota and fecal metabolite profile were analyzed by 16S rRNA sequence and untargeted metabolomics, respectively. As results, GRc significantly alleviated HFD-induced aortic lesions, reduced serum levels of total cholesterol (TC), triglyceride (TG), low-density lipoprotein cholesterol (LDL-C), tumor necrosis factor-α (TNF-α), interleukin (IL)-6 and IL-1β and increased high-density lipoprotein cholesterol (HFD-C) level, as well as the alteration of gut microbiota composition, function and metabolite profile. GRc also reversed HFD change of Bacteroidetes and Firmicutes at phylum level, Muribaculaceae, Lactobacillus, Ileibacterium, Bifidobacterium, Faecalibaculum, Oscillibacter, Blautia, [Eubacterium]_coprostanoligenes_group at genus level and 23 key metabolites involved in taurine and hypotaurine metabolism, arginine biosynthesis, ATP Binding Cassette (ABC) transporters, primary bile acid biosynthesis, purine metabolism, tricarboxylic acid (TCA) cycle and glucagon signaling pathways. Additionally, 8 differential intestinal floras at genus level were associated with 23 key differential metabolites involving atherosclerotic injury. In conclusion, our results demonstrated that GRc regulated ameliorated atherosclerotic injury, microbial and metabolomic changes in HFD-induced ApoE-/- mice, and suggested a potential correlation among gut microbiota, metabolites and atherosclerotic injury regarding the mechanisms of GRc against AS.